2016
DOI: 10.5152/eurjrheum.2015.0010
|View full text |Cite
|
Sign up to set email alerts
|

Teriparatide for the rapid resolution of delayed healing of atypical fractures associated with long-term bisphosphonate use

Abstract: Bisphosphonates (BPs) are the most widely used drugs to treat osteoporosis. However, recent reports associated to long-term BPs use with atypical low-impact fractures and prodromal pain. It is estimated that 26% of the cases of atypical fractures associated with the long-term use of BPs show delayed healing or nonunion. Teriparatide [PTH1-34] (TPTD) is an anabolic drug shown to be effective in stimulating bone formation. The aim was to describe the course of a right diaphyseal femoral fracture sustained by a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Teriparatide treatment was found to refresh bone remodeling after bisphosphonates use and possibly be effective in promoting bone healing [ 14 , 15 ], although the definite mechanism has not been elucidated. Several case reports [ 16 20 ] and series studies [ 21 , 22 ] have mentioned the benefits of teriparatide for patients with atypical fracture. Nevertheless, more data on the treatment outcome of atypical fracture is urgently needed to clarify this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Teriparatide treatment was found to refresh bone remodeling after bisphosphonates use and possibly be effective in promoting bone healing [ 14 , 15 ], although the definite mechanism has not been elucidated. Several case reports [ 16 20 ] and series studies [ 21 , 22 ] have mentioned the benefits of teriparatide for patients with atypical fracture. Nevertheless, more data on the treatment outcome of atypical fracture is urgently needed to clarify this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Displaced AFFs also can be treated successfully with IMN and discontinuation of BMAs; however, some earlier reports have indicated that revision was required in 46% (7/17) of patients owing to nonunion/delayed union [ 2 ] and that the mean time to bone union was 11.3 months for displaced AFFs [ 9 ]. Another report demonstrated that teriparatide (TPTD) combined with IMN is advantageous, although TPTD is contraindicated in cancer patients with bone metastasis [ 10 ]. On the other hand, hip arthroplasty after IMN breakage has been reported to provide good results [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several cases have been reported in the literature where TPP had been used to treat incomplete or complete AFF (Table 2) [3][4][5][6][7][8]; however, none of them showed the effect of TPP on reducing the cortical thickening. We hereby presented a case of preventing near AFF with clinical symptoms; cortical thickness; no obvious radiographic radiolucent line and bone marrow edema by reducing cortical thickness with TPP use.…”
Section: Discussionmentioning
confidence: 99%
“…Mastgalia et al, 2012 [5] A 57-year-old Argentine woman with a sustained non healing femoral shaft fracture 7 years Her pain improved after 10 days of TPP and healing was complete after 3 months.…”
Section: Yearsmentioning
confidence: 99%